Angular: Creating and Hosting a Full-Stack Site. - Wassell, Shaun (linkedin.com, 2020)
Build a full-stack, Angular-powered website from scratch. Learn how to combine this key enterprise JavaScript framework with hapi, MySQL, Google Cloud, and more.